Patterns of Mycobacterium tuberculosis genotypes and resistance mutations in patients with pulmonary multidrug-resistant tuberculosis in Sverdlovsk Oblast, Russia - Umpeleva, Tatiana; Mazurina, Elena; Lavrenchuk, Leonid; Hinderaker, Sven G.; Heldal, Einar; Mariandyshev, Andrei; Vakhrusheva, Diana; Vasilieva, Irina (Frontiers in Tuberculosis, 2025)
BackgroundNearly half of new tuberculosis patients in Sverdlovsk Oblast were diagnosed with multidrug-resistant tuberculosis (MDR-TB) and often exhibited fluoroquinolone resistance (FQ-R). This study aimed to (1) determine the number of MDR-TB patients who had Mycobacterium tuberculosis exhibiting the same genetic patterns (a unique combination of genotypes and mutations in genes associated with drug resistance) using the Russian microarray assay TB-TEST and (2) assess the correlation between these patterns and patient characteristics.Materials and methodsWe analyzed 345 MDR-TB DNA samples from patients with pulmonary TB in Sverdlovsk Oblast between 2017 and 2020 using the TB-TEST. We assumed that isolates with unique patterns, which were seen in only one patient, indicated minimal transmission of M. tuberculosis, while the presence of more isolates with the same pattern suggested a more recent transmission. All patients were categorized into three groups to ensure that each group was approximately of the same size: Group 1 consisted of unique patterns; Group 2 (the low-frequency patterns group) included patterns shared by 2–6 patients; and Group 3, (the high-frequency patterns group, “dominant”) included patterns shared by 7–18 patients.ResultsIn total, 174 distinct genetic patterns were identified: Group 1 included unique patterns, accounting for 36.8%; Group 2 included low-frequency patterns, accounting for 31.0%; and Group 3 included high-frequency patterns, accounting for 32.2%. The Beijing B0/W148 genotype was found in 72.4% of cases, and it was significantly less frequent in patients with unique patterns (59.1% vs. 66.4% vs. 93.7%). Mutations in gyrA/B genes were found in 50.4% of all samples; however, these mutations were significantly more common in the group with unique patterns (73% vs. 43.9% and 30.6%). This suggests that the mutations in gyrA/B genes may have developed over the years because of inadequate chemotherapy regimens. Nevertheless, these mutations have not yet spread widely, possibly due to lower transmission potential or recent emergence. Patients with M. tuberculosis–positive sputum who had undergone treatment for more than 12 months demonstrated a significantly higher proportion of unique patterns and a higher rate of fluoroquinolone resistance.ConclusionPatients with unique patterns were found to have MDR-TB. However, a higher proportion of M. tuberculosis with mutations in gyrA/B genes in the group with unique patterns may indicate reduced transmissibility.